Stiffness at shear-wave elastography and patient presentation predicts upgrade at surgery following an ultrasound-guided core biopsy diagnosis of ductal carcinoma in situ. Issue 11 (November 2016) - Evans, A.; Purdie, C.A.; Jordan, L.; Macaskill, E.J.; Flynn, J.; Vinnicombe, S.
Abstract : Aim: The aim of this study is to establish predictors of invasion in lesions yielding an ultrasound-guided biopsy diagnosis of ductal carcinoma in situ (DCIS). Materials and methods: Patients subjected to ultrasound-guided core biopsy yielding DCIS were studied. At shear-wave elastography (SWE) a threshold of 50 kPa was used for mean elasticity (Emean ) to dichotomise the elasticity data between invasive and non-invasive masses. Data recorded included the mammographic and ultrasound features, the referral source, and grade of DCIS in the biopsy. The chi-square test was used to detect statistical significance. Results: Of 57 lesions, 24 (42%) had invasion at excision. Symptomatic patients and patients with stiff lesions were more likely to have invasion than patients presenting through screening and with soft lesions (58% [14 of 24] versus 30% [10 of 33], p =0.03) and (51% [20 of 39] versus 22% [4 of 18], p =0.04). No other factors showed a relationship with invasion. Combining the two predictors of invasion improved risk stratification with symptomatic and stiff lesions having a risk of invasion of 67% (12 of 18) and soft lesions presenting at screening having only a 17% (2 of 12) risk of invasion ( p =0.02). Conclusion: Stiffness on SWE and the referral source of the patient are predictors of occult invasion in women with an ultrasound-guided core biopsy diagnosis of DCIS. Highlights: Stiffness on SWE predicts occult invasion in women with a US guided biopsy diagnosis of DCIS. Whether a patient has symptoms also predicts the presence of occult invasion. Combining these factors allows stratification of invasion risk.